Gothic Nation: Hawthorne, Ligotti, and the Absent Center of the Nation-State. Issue 2 (1st November 2015) - Unknown
Abstract : Although composed before 9/11, Nathaniel Hawthorne's 'My Kinsman, Major Molineux' and Thomas Ligotti's 'The Shadow at the Bottom of the World' are both prescient in their critique of the impulse of American communities following 9/11 to monumentalise and concretise the nation-state and in particular the remains at Ground Zero. In this essay I discuss Ground Zero as a suggestive trope for the illusiveness of the nation as an' imagined community'. These complementary Gothic short stories operate as allegory and offer a way of reading how patriotic communities cohered around what remained at Ground Zero and (re)produced it as a site of patriotic performance. A new Gothic trait in our age of terror(ism) is the anxiety over the absence of a stable centre that anchors national continuity. This article places these short stories in conversation with Benedict Anderson, Étienne Balibar and other theorists who engage critiques of nation-building in order to draw out what is Gothic about the nation-state and to further substantiate how 9/11 revealed the nation-state as a principally Gothic phenomenon.